Moderating Role of Organizational Learning Culture Between Transformational Leadership and Employees’ Job Satisfaction in Nepali Public Utility Sector - Basnet, Bhupindra Jung; Neupane, Rabindra Kumar (Nepal Journal of Multidisciplinary Research, 2025)
Background: In the workplace, transformational leadership is fundamental in influencing employee attitudes. Organizations can increase productivity by knowing how TL affects employees' job satisfaction moderated by OLC. Objectives: This study was to scrutinize the impact of TL and OLC on EJS, and the moderating influence of OLC between TL between EJS in Nepali public utility sector. Methods: The research designs of descriptive and causal comparative have been applied. The study utilized a sample of 388 permanent employees. Process Macro model one have been used to test objectives. Findings: The results revealed that TL and OLC positively and significantly impacted EJS. The affiliation between TL and EJS is positively moderated by OLC. Conclusion: Transformational leadership has a quality such as future mission, communication culture that are utilized in the organization automatically boosting employees’ job satisfaction. Formal processes, policies, and a democratic management style are all part of OLC, which naturally increases employees' job satisfaction. OLC plays a significant part in strengthening the bond between TL and EJS. Novelty: The connection between TL and EJS that is favorably mediated by OLC is empirically supported by this investigation. This study provides insightful information for managers and policymakers by highlighting the substantial influence of TL on employees' job satisfaction, which is moderated by OLC.